3000PA-Towards a National Reference Corpus of German Clinical Language. - Hahn, U.; Matthies, F.; Lohr, C.; Loffler, M. (Stud Health Technol Inform, 2018)
We introduce 3000PA, a clinical document corpus composed of 3,000 EPRs from three different clinical sites, which will serve as the backbone of a national reference language resource for German clinical NLP. We outline its design principles, results from a medication annotation campaign and the evaluation of a first medication information extraction prototype using a subset of 3000PA.
Keywords: Humans; *Information Storage and Retrieval; Language; *Natural Language Processing